Step-Up Multiple-Input Battery Integrated High-Gain DC-DC Converter for Renewable Energy Application - Azuka, Affam (UNIMAS, 2025)
The challenges faced by renewable energy (RE) sources like solar and wind energy, are a limitation to their potential as viable replacement to fossil fuels in the foreseeable future. Top of these are the problems of irregular or unpredictable availability and low output voltage levels. Multiple input DC-DC converters (MIC) provide the liberty to apply more than one RE source in order to ameliorate the shortcomings. For hybrid RE systems (HRES), it is required that the DC voltage at the inverter level is within the 300 Volts (V) to 450 V range. This means that MICs should deliver a high voltage gain during operation. In addition, the stochastic nature of RE sources mean that MICs be fitted with battery storage capability to handle periods of power unavailability or abundance. Such HRES should have an optimal energy management profile. In this project, a three-input DC-DC converter has been proposed using the non-coupled inductor and boost technique. The aim of this project is to design a three-input converter that produces a high voltage gain, and possesses bidirectional battery storage and two unidirectional ports. The configuration is developed. Three operation modes are obtained for the three-inductor topology and the respective output voltage equations derived. The proposed topology has been investigated theoretically and simulated via the MATLAB/Simulink platform. Software and hardware integration of a designed prototype has been carried out using dSPACE DS1104 digital controller board to generate switching signals. The prototype converter is able to deliver a measured output voltage of 315 V with input voltage of 12 V and 24 V for two input sources in the primary operation mode. The battery discharging during the second operation mode supported a meagre 1.11 % reduction in output voltage despite decreased input voltage levels from the RE sources. Charging the battery during the third operation mode produced a 4.35 % decrease in output voltage. The energy management algorithm proposed can deliver power via single, double or triple source depending on load status. The artificial neural network controller adapted for control of the primary operation mode showed good voltage regulation by eliminating overshoots and reducing the settling time by 30 %. The RE sources are able to individually or simultaneously charge the battery while delivering energy to the load. All the input sources are able to deliver power to the load depending on the integrity of supply. Finally, the simulations and experiments conducted show proof of concept for the developed converter.